PENGGUNAAN MALTODEKTRIN UNTUK MENINGKATKAN MASA SIMPAN LIKOPEN BUAH SEMANGKA (CITRULLUS VULGARIS SCHARD) - sukriadi, sukriadi; Mappiratu, Mappiratu; Nurhaeni, Nurhaeni (Natural Science: Journal of Science and Technology, 2013)
Research using maltodextrin as the coating in order to increase the shelf life of watermelon lycopene has been done. This study aims to estimate the shelf life of watermelon lycopene capsules in packaging with the addition of maltodextrin coating. Achievement of the goals has been the separation of lycopene from watermelon flesh, followed by drying the product of lycopene using solar dryers, extraction of pure lycopene lycopene separation using a solvent mixture of N coarse-Hekasana: Aceton with a ratio of 2: 1, followed by mixing pure lycopene with adsorbent maltodextrin with a ratio of 25: 75% and storage in an oven at 40 and 50oC. Lycopene levels are determined every 24 hours for 10 days using the spectrophotometric method. The resulting data is used to predict the shelf life of lycopene in capsule packaging. The results obtained indicate a shelf life of lycopene at 15, 20, 25, 30, 35, 40, 45, 50, 55, and 60 ° C  are 631, 549, 478, 416, 362, 315, 276, 240, 209 and 181 days respectively.